Trace metal and organic biosignatures in digitate stromatolites from terrestrial siliceous hot spring deposits: Implications for the exploration of martian life - Nersezova, Ema E. (2024)
Novel biosignatures of laminated, microbial, digitate sedimentary structures – stromatolites – from modern geothermal fields of the Taup¯o Volcanic Zone, New Zealand, and from El Tatio, Chile, provide an opportunity to investigate evidence of extremophile life preserved in siliceous hot spring deposits, or sinters, interpreted as analogs for early life on Earth and possibly Mars. Synchrotron-μXRF, electron microprobe analysis, Raman spectroscopy, and optical microscopy are used in a coordinated approach to identify corroborating textural and chemical (organic, inorganic) evidence of life in these modern, opaline (amorphous) siliceous materials. Fluid mobile elements, such as As and Sr, track the growth history of the digitate structures. Trace element enrichments of Ca, Al, Ga, +/ Fe, Mn, As, Rb, Cs, and Sr, are identified in silicified sheaths of microbial filaments embedded within the sinter. In contrast, silicified diatoms in some sinter samples show no trace element enrichment. Gallium enrichments have also been observed in other 16 ka and Jurassic (150 Ma) microbial palisade sinter textures, suggesting the potential for preservation through geologic time, even after recrystallization to quartz. Raman analysis reveals spectra of organics, consistent with pigments for UV protection in cyanobacteria, in silicified sheaths around microbial filaments and are co-located with trace metal enrichments in digitate structures. Due to spectral bands, the location of these molecules (i.e., in the sheaths), and the sampling locations, we ascribe the spectra to scytonemin and carotenoid class molecules. The combined analytical approach outlined here provides a robust means to assess the validity of novel biosignatures, with application to the exploration of Mars, where preservation of opaline silica in >3.6 Ga deposits has the potential to preserve a range of microbial biosignatures.